The Value of Provocative Tests in Diagnosis of Acute and Chronic Cervical Radiculopathy - Majid Ghasemi; Khodayar Golabchi; Seyed Ali Mousavi; Ziba Farajzadegan; Vahid Shaygannejad (مجله دانشکده پزشکی اصفهان, 2011)
Background: The aim of this study was to assess the accuracy of shoulder abduction test (SAT), spurling test (ST) and upper limb tension test (ULTT) in diagnosis of acute or chronic cervical radiculopathy (CR) based on an electrodiagnostic reference criterion. Methods: Our tests and electromyography were done on 97 patients suffering from arm and neck pain. They were classified according to electrodiagnostic findings. Then diagnostic values of provocative tests were assessed in diagnosis of acute or chronic CR on the basis of reference criterion. Findings: SAT and ST were more specific compared to ULTT while ULTT was more sensitive than those two. SAT and ST had a significant accuracy for comparison between acute and chronic CR (P < 0.05). Conclusion: The ULTT is suitable for screening of CR, but SAT and ST can support diagnosis. The SAT and the ST are good diagnostic tests for comparison between acute and chronic CR.